2019
DOI: 10.1101/568618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant photoreceptors and their signaling components compete for binding to the ubiquitin ligase COP1 using their VP-peptide motifs

Abstract: Plants sense different parts of the sun's light spectrum using specialized photoreceptors, many of which signal through the E3 ubiquitin ligase COP1. Photoreceptor binding modulates COP1's ubiquitin ligase activity towards transcription factors. Here we analyze why many COP1-interacting transcription factors and photoreceptors harbor sequence-divergent Val-Pro (VP) peptide motifs. We demonstrate that VP motifs enable different light signaling components to bind to the WD40 domain of COP1 with various binding a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
85
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(99 citation statements)
references
References 106 publications
(120 reference statements)
14
85
0
Order By: Relevance
“…A BLADE‐ON‐PETIOLE 1 (BOP1)‐ and BOP2‐based E3 ubiquitin ligase complex has been shown to ubiqitinate PIF4, thereby affecting photo‐ and thermomorphogenesis (Zhang et al , ); however, involvement of this complex in degradation of PIF4 under UV‐B remains to be demonstrated. Activity of COP1, on the other hand, is a direct target of UVR8 (Favory et al , ; Podolec and Ulm, ; Lau et al , ), and COP1 has been shown to facilitate the stability of PIF family proteins, including PIF4 and PIF5, in the dark (Bauer et al , ; Gangappa and Kumar, ; Pham et al , ). This UVR8‐mediated inhibition of COP1 may thus be linked to degradation of PIF4 and PIF5, although via a currently unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A BLADE‐ON‐PETIOLE 1 (BOP1)‐ and BOP2‐based E3 ubiquitin ligase complex has been shown to ubiqitinate PIF4, thereby affecting photo‐ and thermomorphogenesis (Zhang et al , ); however, involvement of this complex in degradation of PIF4 under UV‐B remains to be demonstrated. Activity of COP1, on the other hand, is a direct target of UVR8 (Favory et al , ; Podolec and Ulm, ; Lau et al , ), and COP1 has been shown to facilitate the stability of PIF family proteins, including PIF4 and PIF5, in the dark (Bauer et al , ; Gangappa and Kumar, ; Pham et al , ). This UVR8‐mediated inhibition of COP1 may thus be linked to degradation of PIF4 and PIF5, although via a currently unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…indicating that the crosstalk between UV-B/UV-A sw and UV-A lw /blue signaling pathways may 561 involve RUPs. In addition, a recent study demonstrated that both UVR8 and CRYs use VP motifs to 562 compete for binding the WD40 domain of COP1 (Lau et al, 2019). Therefore, crosstalk between 563 the two signaling pathways could involve COP1.…”
Section: Transcript Abundance After 6 H and 12 H 481 482mentioning
confidence: 99%
“…However, the exact structural mechanisms underlying this photoreceptor–COP1–substrate tripartite interaction and how the evolutionarily distinct photoreceptors converge on the single hub protein COP1 remained unclear. In this issue of The EMBO Journal , a study from the Roman Ulm and Michael Hothorn's groups at University of Geneva solved, at least partially, these structure‐function problems (Lau et al , ).…”
Section: A Model Depicting How Photoreceptors Regulate Cop1 To Promotmentioning
confidence: 99%
“…An earlier study showed that three COP1‐interacting proteins bear a common sequence motif, referred to as VP, which contains two amino acids, valine–proline, as the invariable core, and that the VP motif may be a common COP1‐binding site (Holm et al , ). Lau et al () showed that six transcription factors (HY5, HYH, CO, COL3, STO, and HFR1) and three photoreceptors (CRY1, CRY2, and UVR8) all possess the VP motifs. They examined the crystal structures of the complexes of the WD40 domain of COP1 (326 residues) and individual VP motifs (< 10 residues) of those nine COP1‐interacting proteins, demonstrating that the core residues of the VP motifs form the center of the COP1‐binding site, whereas the chemically diverse residues at the −3 and −2 position of the VP motifs act as anchor residues by inserting deeply into the VP‐binding cleft of COP1.…”
Section: A Model Depicting How Photoreceptors Regulate Cop1 To Promotmentioning
confidence: 99%